Fictitious Enemy Images and Veiled Violence. Linguistic Analyses of an Interview with an Islamist - Greule, Albrecht; Reimann, Sandra; Schuster, Anna (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
This article examines an interview of two journalists with Erhan A., a confessor of the IS, which appeared in the magazine of the Süddeutsche Zeitung (No. 40, 2014, 13–19). The aim is to bring out Islamist thought patterns through conspicuous features in the choice of words. The moment of repetition (“language patterns”) in the examples is decisive for the selection of the analysis categories. Special features which result from the interview structure are taken into account. The focus of the analysis is on the verbalization of collective names and veiled violence. The identified (semantic) vagueness results from passive constructions and, for example, from indefinite pronouns. In a superior sense, it is a linguistic work on the German language used in Islam or in the narrower sense on the use of the German language in statements by advocates of the so-called Islamic State (IS).